Benzene-associated immunosuppression and chronic inflammation in humans: a systematic review. (16th September 2020) - Guo, Helen; Ahn, Stacy; Zhang, Luoping
Abstract : Objective: Recent evidence has accumulated that the immune system is intimately intertwined with cancer development. Two key characteristics of carcinogens in which the immune system plays a central role are chronic inflammation and immunosuppression. In this systematic review, we investigated the association of chronic inflammatory and immunosuppressive outcomes with benzene, a widely used industrial chemical. Benzene has been confirmed to cause acute myeloid leukaemia and suspected to cause non-Hodgkin lymphoma, two cancers of the blood-forming system that affect immune cells. Methods: We systematically searched PubMed and Embase for all relevant studies using a combination of Medical Subject Headings (MeSH) and selected key words. The detailed review protocol, including search strategy, was registered with PROSPERO, the international prospective register of systematic reviews (#CRD42019138611). Results: Based on all human studies selected in the final review, we report new evidence of a benzene-induced immunosuppressive effect on the adaptive immune system and activation of the innate immune system to cause inflammation. In particular, benzene significantly lowers the number of white blood cells, particularly lymphocytes such as CD4 + T-cells, B-cells and natural killer cells, and increases proinflammatory biomarkers at low levels of exposure. Conclusion: To the best of our knowledge, this is the first comprehensive review of benzene's immunotoxicity in humans. Based on results obtained from this review, we propose two potential immunotoxic mechanisms of how benzene induces leukaemia/lymphoma: (1) cancer invasion caused by proinflammatory cytokine production, and (2) cancer promotion via impaired immunosurveillance. Further studies will be required to confirm the connection between benzene exposure and its effects on the immune system.